Immunogenicity and safety of DTPW-HEPB-HIB (PRP-T) vaccine (Pentavac) in infants aged 2–7 months: a post marketing phase 4 clinical trial study - H. Masoumi-Asl; A. Nateghian; H.R. Baradaran; E. Jafari; R. Azizian; Mahmoud Faramarzi (Инфекция и иммунитет, 2024)
Background.Vaccines play a critical role in safeguarding public health, particularly for children. It is imperative to proactively address safety concerns to uphold trust in their effectiveness and safety. Skepticism surrounding vaccines can have significant adverse effects on the overall well-being of the entire population, potentially leading to individuals opting out of vital vaccinations, thereby posing risks to public health. Thus, ensuring confidence in vaccine safety remains paramount.Materials and methods.This phase four clinical trial was conducted as a post-marketing study (PMS) on 2 to 7 month old healthy infants (N = 539) to evaluate immunity and safety of Indian pentavalent vaccine containing Diphtheria, Tetanus, Pertussis, Hepatitis B and Haemophilus influenza type b [DTPW-HEP B-HIB (PRP-T)/PENTAVAC] in four different centers at Tehran province. Blood samples were collected from eligible infants before receiving the vaccine (2 months of age) and 1 month after the third dose (7 months of age) to determine antibodies against all antigens in the pentavalent vaccine using ELISA.Results.The results indicated that the immune responses demonstrated seroprotection and protective antibody levels after three doses of the vaccine for Haemophilus influenza b, diphtheria, tetanus, hepatitis B virus andBordetella pertussiswere 99.1%, 98.7%, 99.8%, 99.4% and 69.6%, respectively. Statistical analysis showed that the P-value for all vaccine components was similar (P 0.001). The five most common side effects reported were mild fever (10%), erythema at the vaccination site (9.1%), inflammation (4.3%), pain at the vaccination site (3.3%), and restlessness (2.6%).Conclusion.This study’s findings demonstrated a significant increase in antibody levels against all five vaccine components. In light of these results, it can be concluded that the Pentavalent vaccine is not only effective in enhancing immunity against multiple diseases but also presents minimal risk of side effects in the study population. These findings contribute to the body of evidence supporting the safety and efficacy of vaccines, underscoring their crucial role in protecting public health.